The English Sabbath: a study of doctrine and discipline from the Reformation to the Civil War - Parker, Kenneth L. (Cambridge University Press, 1988)
Sabbatarianism is commonly treated as a puritan characteristic, a theological innovation formulated by precisionists in the 1580s and 1590s, and among the earliest issues dividing conformists and puritans. The English Sabbath challenges this orthodoxy. Using local, ecclesiastical and parliamentary evidence, as well as theological works, Dr Parker traces the origins of this doctrine to medieval scholastic theology and finds a broad consensus on the issue in the Elizabethan and Jacobean Church. Re-examining the Book of Sports controversies and the sabbatarian disputes of the 1630s, the author argues that Laudian propagandists triggered vigorous opposition by denying the orthodoxy of this long-established doctrine and calling its defenders innovators. This propaganda polarized opinion and made sabbatarianism one of the most cherished puritan causes during the Civil War. The book is a significant contribution to current re-appraisals of Tudor and Stuart religious history and to our understanding of the origins of the Civil War.